1998
DOI: 10.1063/1.122722
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-induced crystallization of amorphous silicon on glass substrates above and below the eutectic temperature

Abstract: The achievement of high-quality continuous polycrystalline silicon (poly-Si) layers onto glass substrates by using aluminum-induced crystallization is reported. The crystallization behavior of dc sputtered amorphous silicon on glass induced by an Al interface layer has been investigated above and below the eutectic temperature of 577 °C. Secondary electron micrographs in combination with energy-dispersive x-ray microanalysis show that annealing below this temperature leads to the juxtaposed Al and Si layers ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
187
2
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(191 citation statements)
references
References 13 publications
1
187
2
1
Order By: Relevance
“…Rech et al showed that ZnO:Al films prepared by magnetron sputtering and post deposition wet chemical etching demonstrate an effective light trapping and the textured surface reduces reflection losses at the ZnO:Al/Si-interface with excellent light scattering properties for silicon thin film solar cells and modules [3,4]. Grained polycrystalline silicon (poly-Si) films were prepared on nano-textured glass substrates by epitaxial thickening of seed layers formed by the aluminum-induced layer exchange (ALILE) process [5,6] for poly-Si thin film solar cell application with 8% efficiencies with improved material quality [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Rech et al showed that ZnO:Al films prepared by magnetron sputtering and post deposition wet chemical etching demonstrate an effective light trapping and the textured surface reduces reflection losses at the ZnO:Al/Si-interface with excellent light scattering properties for silicon thin film solar cells and modules [3,4]. Grained polycrystalline silicon (poly-Si) films were prepared on nano-textured glass substrates by epitaxial thickening of seed layers formed by the aluminum-induced layer exchange (ALILE) process [5,6] for poly-Si thin film solar cell application with 8% efficiencies with improved material quality [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] This AIC technique enables us to form large-grain (diameters: 10-100 lm) polycrystalline Si films at relativity low temperatures (420-550 C) through the exchange between the Al and Si layers during annealing. [10][11][12][13][14][15] Moreover, we controlled the orientations of the Al-induced-crystallized Si (AIC-Si) films to either (100) or (111) plane by modulating the annealing temperatures, the thickness of Al and Si layers, and the thickness of Al native oxide (AlO x ) interlayers between Si and Al layers. [13][14][15] CVD of Si layers onto the AIC-Si thin-film is a promising approach to fabricate the low-defect Si layers on glass substrates.…”
mentioning
confidence: 99%
“…An attractive method to prepare such large-grained seed layers is the aluminum-induced layer exchange ͑ALILE͒. [4][5][6][7] The ALILE process is a special form of aluminum-induced crystallization. A substrate/Al/ a-Si stack is transformed into a substrate/poly-Si/ Al͑+Si͒ stack by a simple annealing step below the eutectic temperature of the Al/ Si system ͑577°C͒.…”
mentioning
confidence: 99%